El análisis conceptual de la prevención del vih/sida en méxico: una visión evolutiva en población adolescente - Benavides Torres, Raquel Alicia; Sáenz Soto, Norma Elva; Guerra Ordoñez, Jesús Alejandro; Onofre Rodríguez, Dora Julia (Universidad Autónoma de Nuevo León, 2019)
Introduction Human immunodeficiency virus (HIV) is a retrovirus that infects cells of the human immune system and destroys or impairs their function. Infection with this virus results in the progressive depletion of the immune system, leading to immune deficiency. Acquired immunodeficiency syndrome (AIDS) describes the collection of symptoms and infections associated with acquired deficiency of the immune system. The level of HIV in the body and the appearance of certain infections are used as indicators that HIV infection has progressed to AIDS. HIV infection causes a gradual depletion and weakening of the immune system. This results in an increased susceptibility of the body to infections and can lead to the development of AIDS (UNAIDS, 2005). The Acquired Immunodeficiency Deficiency Syndrome (AIDS) appeared in the 80’s and became a Pandemic illness. Around the world, more than sixteen million people with AIDS have died since 1983, and sixteen thousands people become infected by Human Immunodeficiency Virus (HIV) every day (Joint United Nations Program on HIV/AIDS [UNAIDS], 2002).The estimated number of diagnosed AIDS cases for 2002 in the United States is 886,575. Adult’s and adolescent’s AIDS cases total 877,275, including 718,002 cases in males and 159,271 cases in females, with women accounting for an increasing proportion of people living with HIV and AIDS. In the same period, 9,300 AIDS cases were estimated in children under age 13.